Pengaruh Iklim Organisasi dan Sikap Kerja Terhadap Kinerja Karyawan pada PT Yupiter Baru Jaya - Ferry Fernando; Hikmah (SCIENTIA JOURNAL, 2022)
Developments in the health, tourism, automotive, learning and manufacturing industries have a very tight competition. The purpose of this study is to identify the effect of organizational climate and work attitudes partially and simultaneously on the performance of PT Yupiter Baru Jaya employees. The number in a sample is 113 people and the respondents are employees of PT Jupiter Baru Jaya. In a method used quantitative causal with multiple linear regression analysis. The results of a study prove that organizational climate affects significantly 2.835, greater than t table 1.981 and significant with a sig t number of 0.005 which is smaller than 0.05. On the other hand, work attitude affects significantly. Organizational climate and work attitude have a significant effect to the performance of employees at PT Yupiter Baru Jaya. The relationship of organizational climate has a significant influence partially, after that work attitudes have a significant influence partially and simultaneously organizational climate and work attitudes significantly affect the performance of PT Yupiter Baru Jaya employees.